Quality engineering techniques an innovative and creative process model - Rostamkhani, Ramin; Karbasian, Mahdi (CRC Press, 2020)
In today's industrial and complex world, the progress of change is incredible. The amount of information which needs to be analyzed is very large and time has become more and more limited. Industries and firms of all sizes desire to increase productivity and sustainability to keep their competitive edge in the marketplace. One of the best tools for achieving this is the application of Quality Engineering Techniques (QET). This book will introduce the integrated model and the numerical applications for implementing it.